2019
DOI: 10.1101/670422
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic structure ofHstx2modifier ofPrdm9-dependent hybrid male sterility in mice

Abstract: F1 hybrids between mouse inbred strains PWD and C57BL/6 represent the 37 most thoroughly genetically defined model of hybrid sterility in vertebrates. Hybrid male 38 sterility can be fully reconstituted from three components of this model, namely the Prdm9 39 hybrid sterility gene, intersubspecific homeology of Mus musculus musculus and Mus 40 musculus domesticus autosomes, and the X-linked Hstx2 locus. Hstx2 modulates the extent of 41Prdm9-dependent meiotic arrest and harbors two additional genetic factors re… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…The copyright holder for this preprint this version posted November 13, 2021. ; https://doi.org/10.1101/2021.11.12.468424 doi: bioRxiv preprint the musculus X chromosome (Hstx2, Storchová et al 2004;Bhattacharyya et al 2014;Lustyk et al 2019). A characteristic signal of Prdm9-associated sterility is the overexpression of the X chromosome during early meiosis I (Good et al 2010;Bhattacharyya et al 2013;Campbell et al 2013;Larson et al 2017), a developmental stage where the X chromosome would normally be transcriptionally inactive known as Meiotic Sex Chromosome Inactivation (MSCI, Turner 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted November 13, 2021. ; https://doi.org/10.1101/2021.11.12.468424 doi: bioRxiv preprint the musculus X chromosome (Hstx2, Storchová et al 2004;Bhattacharyya et al 2014;Lustyk et al 2019). A characteristic signal of Prdm9-associated sterility is the overexpression of the X chromosome during early meiosis I (Good et al 2010;Bhattacharyya et al 2013;Campbell et al 2013;Larson et al 2017), a developmental stage where the X chromosome would normally be transcriptionally inactive known as Meiotic Sex Chromosome Inactivation (MSCI, Turner 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Fertility in this HMS system can be rescued by decreasing the extent of asymmetric PRDM9 binding through transgenic rescue ( Mihola et al 2009 ), replacing the dom2 allele with dom3 or humanized Prdm9 alleles ( Flachs et al 2012 , 2014 ; Davies et al 2016 ), or by artificially creating random stretches of symmetric homology between certain chromosome pairs ( Gregorova et al 2018 ). The M. m. musculus allele of Hstx2 ( Dzur-Gejdosova et al 2012 ; Bhattacharyya et al 2014 ; Balcova et al 2016 ; Lustyk et al 2019 ) is necessary for HMS in all of the reported M. m. musculus x M. m. domesticus hybrids, though the nature of its interaction with Prdm9 remains uncharacterized.…”
mentioning
confidence: 99%
“…The ZnF DNA-binding domain is among the most rapidly evolving protein-coding regions known in vertebrates, in contrast to other ZnF proteins where these domains are mostly conserved (NAJAFABADI et al 2015;WOLF et al 2020). Second, it is the only mammalian hybrid sterility gene identified to date (MIHOLA et al 2009;BHATTACHARYYA et al 2013;LUSTYK et al 2019). Third, its loss was thought to lead to unconditional infertility, but the growing list of exceptions to this rule suggests modifiers and different degrees of dependence on PRDM9 for successful meiosis among mammalian species, subspecies, and populations (NARASIMHAN et al 2016;MIHOLA et al 2019;POWERS et al 2020).…”
Section: Discussionmentioning
confidence: 99%